The effects of derivative usage on non-financial firms’ risk management - Ting, He (2019)
The company's rationale for using derivatives instruments will have an impact on the suitability of financial reporting rules for these financial tools. Empirically, there is little literature on how these tools affect corporate exposure. This paper is based upon the assumption of firm using derivatives instruments to hedge risk, aiming to identify the correlation between firm-specific risk and the derivatives usage and try to find whether using derivatives can actually reduce firm risk. We firstly analyze the corporate risks associated with the adoption of derivatives. Secondly, the correlation between risk effect and the level of financial derivatives used by Chinese non-financial firms is studied. In order to accomplish this research topic, 274 non-financial firms are chosen from Hong Kong Stock Exchange as the sample by ranking the market capitalization of firms at the end of 2018. Our findings show consistency with the research results that companies employ derivatives to hedge firm-specific risk instead of increasing it. Firm risk, calculated from CAPM model, falls after derivatives are used. Besides, our results show that the extent of derivatives usage also has impact on firm risk. This result is consistent with previous literature. High levels of derivatives users will reduce more corporate risk. Therefore, our conclusion is that the more derivatives instruments employed by firms are, the more effectively firm risk reduces.